A conformação da paisagem da Vila Urlândia - Santa Maria/RS e a percepção ambiental da população residente - Werner, Priscila Vaqueiro Nascimento (2012)
The present study aimed to understand the relationship existing between the shaping of the landscape of the village Urlândia, in Santa Maria/RS, and the environmental perception of the resident population. The selection of the area for research due to the fact that this region passed by several modifications in the recent years, like the increase of resident population, the creation of urban units, the alteration of the urban division of Santa Maria, the actions of the Plan of Acceleration of Growth (PAC) and the irregular occupation. The methodology comprised the realization of field researches in order to observe the landscape of the village; to make interviews with dwellers and public agencies; to realize the physical characterization of the area and the bacteriological analysis of stream water from the village. In order to understand the environmental perception of residents, an environmental and socioeconomic questionnaire was applied. The results obtained confirmed that the landscape of the village Urlândia has been intensely degraded, mainly owing to occupation of the floodplains of the arroyos; inappropriate disposal of the residential sewage; little interest of the public representatives and the community, which values merely the infrastructure aspect, not considering the environmental problems of the village. Based on the study of perception, which works with intentionality and feelings, we can understand, in part, the influence of residents in the current configuration of the landscape. So, it is possible to conclude that the actions and reactions of landscape elements are not individualized, because each influences the other. The effects are positive when the elements are in equilibrium; and they are negative when the society induces environmental degradation. Key words: landscape ecology, environmental perception, environmental degradation